Empathic handover: how would you feel? Handing over dementia experiences and feelings in empathic co-design. Issue 4 (2nd October 2018) - Smeenk, Wina; Sturm, Janienke; Eggen, Berry
Abstract: It is difficult to inform design with experiences from people with dementia. When it comes to involving this vulnerable user group and connecting multidisciplinary design teams, current empathic co-design methods and tools are scarce, seem fragmented and lack a coherent and structured approach. In response, we provide guidance to design teams by proposing a novel, empathic co-design approach that enables a user researcher, who encounters people with dementia, to transfer insights to team members who do not. Our proposal addresses three sequential co-design activities facilitated by an empathic principal designer: (1) individual harvest meetings, (2) collective handover workshops and (3) empathic ideation workshops. Using a case study involving a dementia simulator, we illustrate how the approach contributes to understanding users, transferring insights and translating empathy into design. The positive evaluation of the simulator led us to conclude that the approach not only guided the design team by offering a practical and coherent process, but also enabled individual team members to be receptive, inclusive and committed to people with dementia.